Pengaruh Media Flashcard Terhadap Pengetahuan Siswa Tentang Membuang Sampah Pada Tempatnya - Sirojudin, Vanny Yahdiyani; Herdhianta, Dhimas (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Background: The waste problem is a complex issue that has not been resolved optimally from government to government in Indonesia. In 2020 the total national waste production has reached 67.8 million tons. Based on data from 2021, the total amount of waste production in West Java is 15,735.36 tons per day with the highest value from Bandung City of 1,529.04 tons per day. One of the efforts to handle or minimize the waste problem is by implementing Clean and Healthy Living Behavior (PHBS). Diarrhea is one of the diseases related to PHBS and often affects school-age children. In 2018 the most cases of diarrhea in West Java Province were found in the age group 5-14 years, there were 12,806 cases of diarrhea and the prevalence rate was 7.72%. Therefore, it is necessary to provide education to elementary school students about disposing of garbage in its place through flashcard media. Method: This study used a quasi-experimental design with a one group pretest-posttest without control design to a total sample of 45 students. Data analysis used the Wilcoxon Signed Rank Test to prove the research hypothesis. Result: The average score of students' knowledge before being given flashcard media is 48.82. The average score of students' knowledge after being given flashcard media is 74.20. The percentage increase in knowledge is 51.98%. The p value on student knowledge before and after being given flashcard media is (p=0.000). Conclusion: There was a significant increase in knowledge after being given an intervention through flashcard media on the knowledge of SDN 174 Pasir Impun Bandung City students about disposing of garbage in its place. Keywords: Flashcard; Knowledge; Disposing of Garbage in its Place.